Vector competence of populations of Aedes aegypti from three distinct cities in Kenya for chikungunya virus. - Sheila B Agha; Edith Chepkorir; Francis Mulwa; Caroline Tigoi; Samwel Arum; Milehna M Guarido; Peris Ambala; Betty Chelangat; Joel Lutomiah; David P Tchouassi; Michael J Turell; Rosemary Sang (Public Library of Science (PLoS), 2017)
In April, 2004, chikungunya virus (CHIKV) re-emerged in Kenya and eventually spread to the islands in the Indian Ocean basin, South-East Asia, and the Americas. The virus, which is often associated with high levels of viremia in humans, is mostly transmitted by the urban vector, Aedes aegypti. The expansion of CHIKV presents a public health challenge both locally and internationally. In this study, we investigated the ability of Ae. aegypti mosquitoes from three distinct cities in Kenya; Mombasa (outbreak prone), Kisumu, and Nairobi (no documented outbreak) to transmit CHIKV.Aedes aegypti mosquito populations were exposed to different doses of CHIKV (105.6-7.5 plaque-forming units[PFU]/ml) in an infectious blood meal. Transmission was ascertained by collecting and testing saliva samples from individual mosquitoes at 5, 7, 9, and 14 days post exposure. Infection and dissemination were estimated by testing body and legs, respectively, for individual mosquitoes at selected days post exposure. Tissue culture assays were used to determine the presence of infectious viral particles in the body, leg, and saliva samples. The number of days post exposure had no effect on infection, dissemination, or transmission rates, but these rates increased with an increase in exposure dose in all three populations. Although the rates were highest in Ae. aegypti from Mombasa at titers ≥106.9 PFU/ml, the differences observed were not statistically significant (χ2 ≤ 1.04, DF = 1, P ≥ 0.31). Overall, about 71% of the infected mosquitoes developed a disseminated infection, of which 21% successfully transmitted the virus into a capillary tube, giving an estimated transmission rate of about 10% for mosquitoes that ingested ≥106.9 PFU/ml of CHIKV. All three populations of Ae. aegypti were infectious as early as 5-7 days post exposure. On average, viral dissemination only occurred when body titers were ≥104 PFU/ml in all populations.Populations of Ae. aegypti from Mombasa, Nairobi, and Kisumu were all competent laboratory vectors of CHIKV. Viremia of the infectious blood meal was an important factor in Ae. aegypti susceptibility and transmission of CHIKV. In addition to viremia levels, temperature and feeding behavior of Ae. aegypti may also contribute to the observed disease patterns.